Effect of fibre bundle uncertainty on the tensile and shear behaviour of plain-woven composites. (1st March 2021) - Ma, Dayou; Campos Amico, Sandro; Giglio, Marco; Manes, Andrea
Abstract: The development of woven composites has led to an increase in the number of investigations on the uncertainty of the intricate fibre architecture and its effect on the mechanical properties. The present work proposes a simplified method to study fibre architecture by means of microscopy analysis of cross-sections. The approach is based on multiscale numerical simulations including mesoscale and macroscale models, in which the mesoscale model provide the mechanical parameters exploited as input to the macroscale model, which produces reliable and efficient outputs in engineering applications. Two types of distributions, uniform and normal, were used in the macroscale model to describe the variable fibre architecture parameters, and the normal distribution was found to be more suitable. Both aramid-fibre and glass-fibre woven composites, under two different loading conditions, tension and shear, were investigated, and the results showed the importance of considering the shear behaviour in engineering applications.